Sni'per: a code snippet RESTful API - Queirós, Ricardo (2016)
Today we use the Web for almost everything, even to program. There are several specialized code editors gravitating on the Web and emulating most of the features inherited from traditional IDEs, such as, syntax highlight, code folding, autocompletion and even code refactorization. One of the techniques to speed the code development is the use of snippets as predefined code blocks that can be automatically included in the code. Although several Web editors support this functionality, they come with a limited set of snippets, not allowing the contribution of new blocks of code. Even if that would be possible, they would be available only to the code’s owner or to the editors’ users through a private cloud repository. This paper describes the design and implementation of Sni’per, a RESTful API that allows public access for multi-language programming code-blocks ordered by popularity. Besides being able to access code snippets from other users and score them, we can also contribute with our own snippets creating a global network of shared code. In order to make coding against this API easier, we create a client library that reduces the amount of code required to write and make the code more robust.